Application of Gamma Irradiated Edible Coating in Extending Shelf Life of Fresh Cucumber (Journal of Nuclear Technology in Applied Science, 2026)
This study investigates the enhancement of carboxymethyl cellulose (CMC)/ glycerol (Glyc) edible coatings through gamma irradiation (0, 1, 2, and 3 kGy)  to extend the shelf life of fresh cucumbers. Analytical characterization using  Fourier Transform Infrared (FTIR) confirmed that the primary functional groups  of the CMC matrix remained stable following irradiation. Thermal evaluations  via Thermogravimetric Analysis (TGA), Differential scanning calorimetry (DSC), and Thermomechanical Analysis (TMA) revealed that a 2 kGy dose  provided an optimal for thermal stability due to radiation-induced cross-linking.  Physicochemical results showed that irradiated coatings (3 kGy) significantly  outperformed unirradiated controls in preserving quality throughout a 28- day storage period. Rheological analysis indicated that irradiation reduced the  apparent viscosity of the CMC/Glyc solutions due to the cleavage of glycosidic  bonds, which improved application characteristics. Furthermore, microbiological  testing demonstrated that the 3 kGy irradiated coating acted as a potent  antimicrobial agent.
Keywords: Carboxymethyl cellulose; Gamma irradiation; Thermal analysis; Physiochemical analysis; Rheological analysis